2016
DOI: 10.17795/bhs-34473
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Disorders and Their Related Risk Factors Among Iranian Nurses

Abstract: Background: Work-related musculoskeletal disorders (MSDs) are one of the most occupational problems among nurses and often cause many physical and psychological complications for nurses, and are a financial burden for health-care systems. Objectives: The aim of this study was to determine the prevalence MSDs and their related risk factors among Iranian nurses. Patients and Methods: This descriptive-correlational study included 240 hospital nurses, with a baccalaureate nursing degree, who worked at three public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
1
7

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 24 publications
(45 reference statements)
3
14
1
7
Order By: Relevance
“…This is in line with the reports by MoreiraSilva et al (2013) and Mozafari et al (2014) (34,35). It is also noteworthy that some studies have reported no significant relationship between the body mass index and the incidence of MSDs (33,36). In their study, Lorusso et al (2007) (37) mentioned that the body mass index could make an individual susceptible to developing MSDs.…”
Section: Discussionmentioning
confidence: 93%
“…This is in line with the reports by MoreiraSilva et al (2013) and Mozafari et al (2014) (34,35). It is also noteworthy that some studies have reported no significant relationship between the body mass index and the incidence of MSDs (33,36). In their study, Lorusso et al (2007) (37) mentioned that the body mass index could make an individual susceptible to developing MSDs.…”
Section: Discussionmentioning
confidence: 93%
“…Bernal et al, 2015 describe MSDs as manifestations elicited or aggravated by long term exposure to certain hazards at the workplace including discomfort and pain in body structures, such as muscles, joints, bones, tendons, nerves and supporting blood vessels. Work-related MSDs have adverse outcomes on quality of life, productivity, increase work limitation, absenteeism, transfer to another work, and disabilities (Hagberg et al, 2012 andTaghinejad et al, 2016 (Yip 2001 andSmith et al 2005). These work tasks are usually performed manually without assistance of equipment.…”
Section: Introductionmentioning
confidence: 99%
“…(1) -71,9% (5) ) a experienciar uma LMLET nos últimos 12 meses (1) . A dor e o desconforto músculo-esquelético são uma queixa presente desde os primeiros anos de atividade profissional (6) , causam diversas complicações físicas e psicológicas, provocando absentismo (5) e representam 56% das causas de ausência temporária ao serviço (1) .…”
Section: Introductionunclassified
“…A dor e o desconforto músculo-esquelético são uma queixa presente desde os primeiros anos de atividade profissional (6) , causam diversas complicações físicas e psicológicas, provocando absentismo (5) e representam 56% das causas de ausência temporária ao serviço (1) . A discrepância nos valores da prevalência encontrada, nos diferentes estudos, pode ter sido influenciada pelos métodos, técnicas, procedimentos e tamanho da amostra, mas revelam a magnitude de um problema de saúde ocupacional que demanda um resolução urgente.…”
Section: Introductionunclassified
See 1 more Smart Citation